2015
DOI: 10.1021/acsmedchemlett.5b00363
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and DNA Binding Profile of a Macrocyclic β-Sheet Analogue of ARC Protein

Abstract: ARC repressor (apoptosis repressor with caspase recruitment domain) is a protein which binds selectively to a specific sequence of DNA. In humans, ARC is primarily expressed in striated muscle tissue, which normally does not undergo rapid cell turnover. This suggests that ARC may play a protective role in the prevention against Duchenne Muscular Dystrophy and several types of tumors. In this Letter we report the synthesis, characterization, and conformational analysis of a β-sheet ARC repressor mimetic, based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…The standard SPPS procedure was followed, using 3 equiv of each amino acid for each coupling and HBTU (3 equiv), HOBt (3 equiv), and DIPEA (6 equiv) dissolved in 4 mL of DMF as the coupling mixture. , 120 mg of 2-CT-Cl resin (1 equiv) was weighed into a syringe for manual solid phase synthesis and swelled in DCM (8 mL) for 1 h with an automatic shaker. For the first coupling, 5 mL of a DCM solution containing the first amino acid and DIPEA was added to the resin and shaken overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard SPPS procedure was followed, using 3 equiv of each amino acid for each coupling and HBTU (3 equiv), HOBt (3 equiv), and DIPEA (6 equiv) dissolved in 4 mL of DMF as the coupling mixture. , 120 mg of 2-CT-Cl resin (1 equiv) was weighed into a syringe for manual solid phase synthesis and swelled in DCM (8 mL) for 1 h with an automatic shaker. For the first coupling, 5 mL of a DCM solution containing the first amino acid and DIPEA was added to the resin and shaken overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, teixobactin interacts as β-sheet dimer with cell wall membrane components, thus generating two cavities comprising the C -terminal cycle and N -terminus acting as receptor for pyrophosphate groups via hydrogen bonding . As observed by the X-ray crystallographic structure of teixobactin analogues, a lactam bridge in place of a lactone may improve the interaction with lipids II and III; however, ring expansion resulted in analogues with very poor activity. , The solid state NMR work reported by Shukla and co-workers helps to clarify the importance of the relative stereochemistry and structural features of teixobactin: The use of a labeled analogue reveals the ability of this molecule to form a large cluster on the membrane surface by oligomerization of lipid II-binding teixobactin. This molecule assumes a β-sheet form in which the critical sequence of d - and l -amino acids allows separation of hydrophobic and hydrophilic side chains located at the same side of the β-sheet, a common behavior of diverse naturally occurring peptides. The peptide head containing ring interacts with N -acetyl muramic acid and to a minor extent with N -acetyl-glucosamine; the tail is anchored on the membrane surface by two isoleucines. In this way teixobactin significantly perturbs the bacterial membrane lipids and cell wall biosynthesis. , …”
mentioning
confidence: 99%
“…All these works, however, have been done by creating and screening against a random combinatorial peptide library, and therefore, the obtained peptidic mimotopes are generally weak and exhibit broad specificity. Recently, Stefanucci et al (2015Stefanucci et al ( , 2021 demonstrated that the linear and cyclic βhairpin peptides can be rationally derived from the intermolecular interaction interface between ARC repressor and DNA, which exhibit a potential binding property to the cognate site of DNA major groove.…”
Section: Introductionmentioning
confidence: 99%
“…12 . Cyclic peptidomimetics are usually characterized by: ( i ) folding in a rigid structure 13 ; ( ii ) an improved metabolic stability compared to the linear counterparts 14 ; ( iii ) better penetration of the blood-brain barrier (BBB) 15 ; ( iv ) improved oral bioavailability and rapid excretion 16 ; ( v ) and a better pharmacological profile in terms of potency and selectivity 17 . These features could make DPDPE and other analogues good candidates as leads for drug development, as peptides are generally characterized by high selectivity and low toxicity 18 .…”
Section: Introductionmentioning
confidence: 99%